Managing the Difficult Airway in Adults with Life-Threatening Cervical Infections: A Scoping Review - Andrea Migliorelli; Marianna Manuelli; Andrea Bianchino; Giovanni Cammaroto; Andrea Ciorba; Francesco Stomeo; Stefano Pelucchi; Chiara Bianchini (Healthcare, 2026)
Background: Airway management in patients with cervical infections remains a major challenge because progressive swelling and distortion of the upper airway may rapidly lead to life-threatening airway obstruction. Despite advances in imaging and advanced intubation techniques, the optimal management strategy remains controversial. This scoping review aimed to evaluate the current evidence on airway assessment and management of adult patients with cervical infections. Methods: A scoping review was conducted according to the PRISMA-ScR recommendations. PubMed/MEDLINE, Scopus, and Embase were systematically searched for English-language studies published between January 2006 and May 2026. Studies evaluating airway management in adult patients with deep neck infections or acute infectious epiglottitis/supraglottitis were included. Data regarding study characteristics, airway management strategies, predictors of airway intervention, and clinical outcomes were extracted and synthesized descriptively. Results: Fourteen studies involving 3297 patients met the inclusion criteria. Endotracheal intubation was the most frequently reported airway management strategy, while tracheostomy remained essential in selected patients with extensive multispace infections, descending necrotizing mediastinitis, severe airway alteration, or anticipated prolonged airway protection. Clinical signs of respiratory compromise, multispace cervical involvement, mediastinal extension, and significant supraglottic edema were the most consistently reported predictors of airway intervention. Across the included studies, airway management strategies varied considerably according to disease severity, anatomical findings, institutional protocols, and operator experience. Conclusions: Current evidence suggests an individualized, multidisciplinary approach to airway management in adults with life-threatening cervical infections. Timely airway assessment integrating clinical evaluation, flexible endoscopy, and contrast-enhanced computed tomography is essential to guide appropriate airway intervention.